PENERAPAN IPTEKS TENTANG PENYELESAIAN SENGKETA BATAS TANAH ULAYAT MELALUI JALUR LITIGASI DAN NON LITIGASI PADA MASYARAKAT HUKUM ADAT DI KAMPUNG NENDALI - Daniel Tanati; James Yoseph Palenewen (CV. Multi Kreasi Media, 2022)
This service is carried out under the title Application of IPTEKS regarding the settlement of communal land boundary disputes through litigation and non-litigation in customary law communities in Nendali Village, Sentani Timur District, Jayapura Regency, which was carried out to partners due to cases from partners regarding misunderstanding regarding dispute resolution regarding land boundaries. ulayat so that with the expertise possessed by the servant can carry out the application of the science and technology. The method of implementing this community service is by implementing science and technology through lectures and discussions which will be held on Saturday, July 31, 2021 which will be held at the village hall, as well as assistance to partners, which has been carried out until now. This activity begins with preparation and coordination, then presentation of material on dispute resolution. customary land boundaries through litigation and non-litigation. The output of this service is an increase in partners' knowledge regarding the resolution of disputes regarding customary land boundaries through litigation and non-litigation in order to obtain guarantees of legal certainty.